Logic and Argumentation 5th International Conference, CLAR 2023, Hangzhou, China, September 10-12, 2023, Proceedings - Herzig, Andreas; Luo, Jieting; Pardo, Pere. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 5th International Conference on Logic and Argumentation, CLAR 2023, held in Hangzhou, China, during September 10-12, 2023. The 11 full papers, one short paper and one invited paper presented in this book were carefully reviewed and selected from 20 submissions. The papers focus on topics such as: logic and automated deduction; abstract and structured argumentation; dialogues, games and practical reasoning; and quantitative argumentation.
Logic and Automated Deduction -- Dynamic Modal Logic with Counting: when Reduction Axioms Work and Fail -- Solving Modal Logic Problems by Translation to Higher-order Logic -- Formalizing the Unexpected Hanging Paradox: a Classical Surprise -- Abstract and Structured Argumentation -- Weakest Link in Formal Argumentation: Lookahead and Principle-based Analysis -- A Logical Encoding for k-m-Realization of Extensions in Abstract Argumentation -- Topological Conditions and Solutions for Repairing Argumentation Frameworks -- Dialogues, Games and Practical Reasoning -- Providing personalized Explanations: a Conversational Approach -- Audience irrelevance in Strategic Argumentation Games -- A Structured Bipolar Argumentation Theory for Providing Explanations in Practical Reasoning -- Quantitative Argumentation -- A Filtering-based General Approach to Learning Rational Constraints of Epistemic Graphs -- Fuzzy Labeling Semantics for Quantitative Argumentation -- A Logic for Preference Lifting under Uncertainty and its Decidability.
Keywords: Artificial intelligence; Computer programming; Compilers (Computer programs).; Algorithms; Computer science; Machine theory; Artificial Intelligence; Programming Techniques; Compilers and Interpreters; Design and Analysis of Algorithms; Computer Science Logic and Foundations of Programming; Formal Languages and Automata Theory